Improving Student Activity and Learning Outcomes Through the Application of Text-Based Learning Models - Suryati (International Journal of Management and Education in Human Development, 2022)
The purpose of this study is to know the learning process by using a text-based learning model to increase the activity and learning outcomes of English subjects in class VII students of SMP Swasta Sejahtera in the odd semester of the 2019/2020 school year. Knowing the increase in student activity and learning outcomes in English subjects through the application of a text-based learning model in class VII of SMP Swasta Sejahtera in the odd semester of the 2019/2020 school year. Knowing the impressions of students after taking lessons using the Text-Based Learning Model to increase the activity and learning outcomes of English subjects in class VII of SMP Swasta Sejahtera in the odd semester of the 2019/2020 school year. This research is Classroom Action Research (CAR). CAR is carried out in a 4-step cycle assessment process, namely (1) planning, (2) conducting, (3) observing (observing), and (4) reflecting. This research will be conducted in at least two cycles. Each cycle carried out three meetings. So that this research was carried out for approximately three months (including making a proposal to making a report). The expected result of each cycle is a change in student activity and increased academic competence (learning outcomes). The result showed that The learning process using a text-based learning model is as follows: Stage 1: BKOF (Building Knowledge of Field) which is to build knowledge or background knowledge of students about the text to be discussed, Stage 2: MOT (Modelling of Text), namely providing a text model, Phase 3: JCOT (Join Construction of Text) which is the implementation of students' knowledge and understanding to produce texts in groups, Phase 4: ICOT (Independent Construction of Text) which is the implementation of students' knowledge and understanding to produce texts independently. The implementation from cycle 1 to cycle 2 has improved. This study shows that the activeness of students from the initial conditions, cycle 1 and cycle 2 continues to increase. In the initial conditions to cycle 1 and to cycle 2, the percentage of students whose activity was in the low category continued to decrease, namely 53% - 18% - 0%. Medium category is from 29% - 61% - 11%. Medium category is high from 18% - 21% - 89%. This study shows that student learning outcomes have increased after the action. The percentage of students who have not completed continues to decline from cycle 1 to cycle 2 (from 26.47% to 8.82%). The percentage of students who have completed has increased from cycle 1 to cycle 2 (from 73.53% to 91.18%). The indicator of the success of this CAR is that this CAR is said to be successful if the percentage of students whose learning outcomes are assessed as complete reaches a minimum of 85%. The table shows that the percentage of students whose grades have been completed has reached 91.18%, so this CAR has been successful.